Mapping human rights to democratic policing through the ECHR - Aydin-Aitchison, Andrew (2019)
This article examines how human rights relate to democratic policing. We differentiate policing for democracy, which protects democracy, from democratically responsive policing, where police are governed democratically. Using this two-fold distinction to examine European Court of Human Rights cases, we find a close match between Convention rights and policing for democracy. Regarding democratically responsive policing, the Court provides responsiveness within the structural limits of reacting to individual complaints, and as one element in the broader landscape of governance. Further, cases show how that landscape features in Court judgments. We argue that robust enforcement, and careful attention to case law during drafting and implementation of police legislation and governance arrangements, help protect democracy and enhance democratically responsive policing.WOS:000596737400005Emerging Sources Citation IndexArticleAralık2020YÖK - 2020-2